Path Analysis of the Factors Affecting the Quality of Life of Chronic Kidney Failure Patients Receiving Hemodialysis - Budhiana, Johan; Elengoe, Asita; Saefulaman Mohamed Said, Mohamed (KnE Social Sciences, 2023)
Patients undergoing hemodialysis for chronic kidney failure will experience physical and psychosocial changes that affect their physical, psychological, social, and economic quality of life. Several factors can affect the quality of life of patients with chronic kidney failure, including self-management, self-efficacy, and religiosity. This study aimed to determine the effects of religiosity, self-efficacy, and self-management on the quality of life of hemodialysis patients with chronic kidney failure. This research is a correlational study. The sample size was 71, and the sampling strategy was total sampling. The instrument employs the KDQoL to assess the quality of life, the general self-efficacy (GSE) questionnaire to assess self-efficacy, the hemodialysis self-management instrument (HDSMI) to assess self-management, and the Duke University Religion Index to assess religious affiliation (DUREL). Utilizing path analysis for statistical analysis. Results indicated that the mean and standard deviation of quality of life was 62.76 (8.36), self-management was 51.56 (5.64), self-efficacy was 71.11 (8.44), and religiosity was 21.02. (2.78). Self-management (b = 0.280, p = 0.006), self-efficacy (b = 0.270, p = 0.013), and religiosity (b = 0.425, p = 0.000) have a direct influence on the quality of life. Religiosity indirectly influences the quality of life via self-efficacy and self-management. Through self-management, self-efficacy has an indirect effect on the quality of life. The conclusion is that religiosity, self-efficacy, and self-management can enhance the quality of life for patients with chronic kidney failure. In order for the hospital to improve the patient’s quality of life, intensive education concerning the three variables is therefore anticipated. Keywords: quality of life, religiosity, self-management, self-ef